KEBIJAKAN PUBLIK DALAM PELAKSANAAAN PENATAAN POLA PEDAGANG KAKI LIMA DI KOTA MALANG - Anton Sudjarwo (REFORMASI, 2012)
Development in our country in its core is to alleviate people from the crush of problems in real life. The existence of street vendors (PKL) if it is associated with national development, it is very closely related, moreover if it is associated with a level of prosperity. Therefore it needs to think seriously about problems of street vendors in some areas recently since it has been a very complicated issue for local governments concerned. By the increasing levels of urbanization, it will automatically increase the amount of labors that already exist, and these circumstances will increase the level of good job-competition. The things to think about are the synergy between the numbers of workers with jobs that are available. Because if this problem cannot be overcome successfully, it will be serious problems later